An unprecedented case of dodecamorphism: the twelfth polymorph of aripiprazole formed by seeding with its active metabolite. Issue 9 (21st January 2016) - Zeidan, T. A.; Trotta, J. T.; Tilak, P. A.; Oliveira, M. A.; Chiarella, R. A.; Foxman, B. M.; Almarsson, Ö.; Hickey, M. B.
Abstract : Twelfth polymorph of the anti-psychotic drug aripiprazole was discovered where its active metabolite acted as a template during recrystallization. Abstract : A new polymorph of aripiprazole has been discovered, making it the most polymorphic drug to date with twelve reported anhydrous forms, and a record-breaking ninth solved crystal structure. The new form was induced by seeding with crystals of the active metabolite dehydro-aripiprazole.